2016
DOI: 10.1093/jme/tjw043
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Scorpion Sting in a High-Risk Area of Southern Iran

Abstract: Scorpion sting is a public health problem in south and southwestern parts of Iran, with about 36,000 cases recorded annually. This study aimed to find the spatial distribution of scorpions and their stings in Bandar Abbas County. Monthly scorpion sting cases at the village level were obtained and used for mapping. Scorpions were collected from 14 collection sites using a UV lamp at night and searching under stones during the day time. During the study period, a total of 3,971 cases of scorpion sting were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…While the patient under five years old less faced with this problem. This rate matches the results of [20,24]. In which, the moderate ratio can be seen between the age 6-15 and patient with more than 50 years old.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While the patient under five years old less faced with this problem. This rate matches the results of [20,24]. In which, the moderate ratio can be seen between the age 6-15 and patient with more than 50 years old.…”
Section: Discussionsupporting
confidence: 92%
“…Also in Argentina scorpion-stung patients were 54% males and 46% females [19] .However, it is not consistent with the results of [20] in Ramhormoz, South-West of Iran, they reported more numbers of females than males. Shahi, Moosavy [24] reported that scorpionism in Bandar Abbas between males and females nearly was equal. It is due to different approaches and geographical positions in the two studies.…”
Section: Discussionmentioning
confidence: 98%
“…The diversity of scorpion species is increased in tropical regions in latitudes between 23 and 38 degrees [ 8 ]. Given the geographical coordinates of Iran (between 25 and 40 degrees north), the scorpion distribution and species diversity in the country are remarkable [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…After Mexico, Iran has the highest rate of the scorpion stings in the globe [ 11 ]. The majority of the stings that occur in the country are reported from the province of Khuzestan, followed by Sistan-Baluchistan, and Hormozgan [ 9 ]. About 50 species of scorpions are found throughout the territory and distributed into four families: Diplocentridae, Buthidae, Scorpionidae, and Hemiscorpiidae.…”
Section: Introductionmentioning
confidence: 99%
“…This increase is a health threat in this area, since with the increase of temperature and decrease of humidity, the prevalence of scorpionism increased. In Hormozgan Province, South of Iran (18), Morocco (19), and Brazil (20) scorpionism also increased. More than 70% of the cases occurred in June, July, and August.…”
Section: Discussionmentioning
confidence: 99%